Characterizing the original anti‐C5 function‐blocking antibody, BB5.1, for species specificity, mode of action and interactions with C5. Issue 2 (13th July 2020) - Zelek, Wioleta M.; Menzies, Georgina E.; Brancale, Andrea; Stockinger, Brigitta; Morgan, Bryan Paul
Summary: The implication of complement in multiple diseases over the last 20 years has fuelled interest in developing anti‐complement drugs. To date, the focus has been on C5; blocking cleavage of C5 prevents formation of two pro‐inflammatory activities, C5a anaphylatoxin and membrane attack complex. The concept of C5 blockade to inhibit inflammation dates back 30 years to the description of BB5.1, an anti‐C5 blocking monoclonal antibody raised in C5‐deficient mice. This antibody proved an invaluable tool to demonstrate complement involvement in mouse disease models and catalysed enthusiasm for anti‐complement drug development, culminating in the anti‐human C5 monoclonal antibody eculizumab, the most successful anti‐complement drug to date, already in clinical use for several rare diseases. Despite its key role in providing proof‐of‐concept for C5 blockade, the mechanism of BB5.1 inhibition remains poorly understood. Here, we characterized BB5.1 cross‐species inhibition, C5 binding affinity and chain specificity. BB5.1 efficiently inhibited C5 in mouse serum but not in human or other rodent sera; it prevented C5 cleavage and C5a generation. BB5.1 bound the C5 α ‐chain with high affinity and slow off‐rate. BB5.1 complementarity‐determining regions were obtained and docking algorithms were used to predict the likely binding interface on mouse C5. Abstract : The work provides a mechanistic basis for the activities of this landmark antibody BB5.1, a much‐used tool that was a major impetus to the development of anti‐complement drugs for human disease.